The semiotics study of Al-Ahdhar Mosque architecture using the trichotomy of Charles Sanders Peirce - Taufiq Widodo; Primi Artiningrum (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
Semiotics is a science of signs, which is found daily in public spaces, print media, literary works, and buildings. A building can convey value, story, philosophy, and meaning through signs expressed on its architectural elements. These signs are in form of shape, spatial arrangement, building ornaments, colors, patterns, textures, or other elements. Therefore, this study aims to determine the meaning and message expressed by the architectural form of the Al-Ahdhar Mosque based on Charles Sanders Peirce's Semiotics, which consists of three aspects, namely Representant, Object, and Interpretant with the concept of trichotomy. It was carried out using a descriptive qualitative method to determine more about the observed phenomena. The meaning and messages of the case study were conveyed in form of signs and symbols through architectural elements. The data obtained through observations, interviews, and documentation were translated using Charles Sanders Peirce's Trichotomy semiotics. The modern-style design of the Al-Ahdhar Mosque showed that the forms and architectural elements carry a certain meaning. The results also showed that Charles Sanders Peirce's Trichotomy semiotic theory can be used to reveal meaning through signs. This indicated that signs on building elements have a meaning, and the relationship of meaning, sign, and symbol is from a correlation between signs and omens, which is called the semiosis process.